Robust adaptive formation control of quadcopters based on a leader–follower approach. (16th July 2019) - Xuan-Mung, Nguyen; Hong, Sung Kyung
The formation control problem for multi-agent systems has been explored in recent years. However, controlling a formation of multiple aerial vehicles in the presence of disturbances has been a challenge for control researchers. To deal with this issue, a robust adaptive formation control algorithm for a group of multiple quadcopters is proposed. A nonlinear model of the dynamics of the formation error is obtained based on a leader–follower scheme. This model considers both the relative position in the x – y plane and the relative heading angle between vehicles in the presence of uncertainties. In addition, by means of a model reference control approach, a robust adaptive formation controller is used to steer the vehicles into a formation pattern and have them maintain the formation shape. Numerical simulations demonstrate the effectiveness of the algorithm.